Analisis Pembiayaan Pelayanan Kesehatan Orang Asli Papua Tanpa Jaminan Kesehatan - Lekatompessy, Ransta L; Muskita, Nevile Rymon; Hartono, Risky Kusuma (Universitas Musamus, Merauke, Papua, 2024)
Merauke Regional Referral Hospital in South Papua reported 5,482 visits of OAP patients who do not have health insurance during 2022 with an total cost of IDR 8,859,983,341, - Of course, this will be a problem for Merauke Regional Hospital if there is no adequate budget support to serve the community, especially OAP who have not been registered as JKN participants. Therefore, this study was conducted to analyze the financing of health services for Indigenous Papuans (OAP) without health insurance at Merauke Regional Hospital so that it can provide input or recommendations for regional leaders and the Regional Government Budget Team as well as the South Papua Provincial Health, Population Control and Family Planning Office in determining policies related to budget support for Merauke Regional Hospital for health service financing for unsecured OAP health. This research is a type of qualitative research with a case study approach, where data collection is carried out through document review and interviews. Informants were selected purposively and data were analyzed using Miles and Huberman's interactive model. The results of this study obtained that the financing of OAP health services without health insurance at the RSUD during 2022 experienced a